“SEDEKAH LAUT” TRADITION FOR IN THE FISHERMEN COMMUNITY IN PEKALONGAN, CENTRAL JAVA - Sarjana Sigit Wahyudi (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Tradition of “sedekah laut” (sea thanksgiving) in the Pekalongan fishermen community is also “Nyadran” which is always celebrated every month of “Syuro”. This ceremony is the expression of gratitude to God having given safety and abundance of fortune in fish catching in the sea. In this tradition there are various manings, omens, symbols which can be used as philosophy of life for the fishermen. This tradition is unique and interesting; it is also the regional cultural wealth which should be preserved, especially for thourism interests.